2013
DOI: 10.1089/lap.2011.0123
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience with Magnet-Assisted Single Trocar Appendectomy in Children

Abstract: MAST appendectomy is safe and effective in children. Magnetic instruments provide excellent triangulation and improve ergonomics. This technique uses a single 12-mm trocar and can be performed without the aid of a surgical assistant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…This makes SILA a more challenging technique, especially in the much smaller abdominal cavities of children. Padilla et al [43] reported a modified SILA technique in which magnetic instruments were used to provide excellent triangulation and to improve ergonomics; this technique may eventually play a role in the reduction of the duration of surgery. Additionally, it should also be noted that the ability to overcome the initial steep learning curve associated with the adoption of a new surgical technique as well as practice and experience with single-incision laparoscopic surgeries could also assist in the reduction of the operation time.…”
Section: Study or Subgroupmentioning
confidence: 99%
“…This makes SILA a more challenging technique, especially in the much smaller abdominal cavities of children. Padilla et al [43] reported a modified SILA technique in which magnetic instruments were used to provide excellent triangulation and to improve ergonomics; this technique may eventually play a role in the reduction of the duration of surgery. Additionally, it should also be noted that the ability to overcome the initial steep learning curve associated with the adoption of a new surgical technique as well as practice and experience with single-incision laparoscopic surgeries could also assist in the reduction of the operation time.…”
Section: Study or Subgroupmentioning
confidence: 99%
“…However, in the current study, the problems anticipated for the loss of triangulation were overcome by using a mini-laparoscopic instrument in complicated cases. To overcome the technical challenges associated with the use of single-port or reduced-port laparoscopic surgery, Lasheen et al [ 25 ] used a spiral needle to facilitate the procedure in two-port surgery for appendectomy, and Padilla et al [ 26 ] reported SPLS using a magnet-assisted single trocar for adequate exposure. Moreover, Ates et al [ 27 ] introduced a percutaneously-inserted suture from the right lower quadrant into the peritoneal cavity during SPLS for an appendectomy.…”
Section: Discussionmentioning
confidence: 99%
“…(c) The magnetic anchor grippers assisted in separating cystic duct. (d) Remove the magnetic anchor grippers through the subxiphoid trocar 图 3 磁锚定技术辅助阑尾切除术 [8] Figure 3 Magnetic anchor technique assisted laparoscopic appendectomy [8] 成后, 用腔镜抓钳吸引内置抓钳尾端磁体, 将内置抓钳 牵拉离体. [21] .…”
Section: 磁锚定技术在胸外科的应用mentioning
confidence: 99%